Studies on Detection, Prevalence and Molecular Characterization of Avian Rotavirus - Yaduvanshi, Shalini; Singh, Rashmi; Bhattacharya, Amitav; Ikram, Mohammed; Sircar, Shubhankar; Malik, Yashpal Singh (The Indian Journal of Animal Sciences, 2022)
Rotaviruses are the foremost cause of acute gastroenteritis. Outbreaks of rotavirus infection can lead to significant economic losses in livestock and poultry industry. Group A and D rotavirus are the predominant enteric viruses groups in birds. Limited prevalence studies are available to date in India. Poultry samples consisting of 20 fecal samples and 80 intestinal content samples were screened by VP6 gene based diagnostic PCR for AvRVA and AvRVD. All samples were negative for group A rotavirus. Five fecal samples and 22 intestinal samples were positive for AvRVD-VP6 gene giving an amplicon of 185 bp giving a prevalence of 27%. Positive samples screened for VP4, VP7, NSP4 and NSP5 genes of AvRVD were negative for VP4, VP7 and NSP4 but six samples were positive for NSP5 gene giving an amplicon of 652 bp size. Cloning and sequencing showed 99.4 to 100% sequence similarity among all six isolates at nucleotide level. The percent nucleotide similarity with chicken RVD isolates was in the range 78.2-85.1%. All isolates showed highest similarity of 85% with chicken isolate from South Korea followed by Germany (81.5%) and Australia (78.2%). The phylogenetic analysis exhibited all six isolates clustered together in a separate clade with isolates from Australia, Germany and South Korea.